Fenomena Phone Snubbing pada Siswa Menengah Pertama - Lutfi Fauzan; Elia Flurentin; Lutfi Fauzan; Meytikasari Dwijayanti; Meytikasari Dwijayanti (Universitas Negeri Malang, 2021)
Abstract: In the midst of the Covid-19 pandemic, smartphones have become the main tool in online learning at all levels of education. This has an impact on the intensity of smartphone use in everyday life. This situation has led to a growing phone snubbing behavior and is not realized by individuals. Phone Snubbing as a phenomenon of excessive individual smartphone use shows a behavior that is ignorant and indifferent to the presence of people around. This behavior is characterized by being fixated on a smartphone that is held so that it can have positive and negative impacts in the social environment, especially in the personal and social fields of students. This descriptive qualitative research aims to describe information about the background and factors causing the phenomenon of phone snubbing behavior in students as well as recommendations for BK service strategies. Data analysis using the Miles and Huberman model. The validity of the research data was carried out by extending observations, increasing persistence and triangulating sources. The results showed 1) The background of phone snubbing behavior in junior high school students stated that the use of smartphones in the high category, namely an average of 6-10 hours per day, caused a high smartphone dependence. The situation of using smartphones when interacting with junior high school students is very diverse, including forms of avoidance, to get rid of boredom, the importance of activities with smartphones, and other needs that require a fast response. The reason for using a smartphone is to fulfill the interests of learning as well as for entertainment, maintaining communication with long distance friends. 2) Four factors that indicate phone snubbing behavior of junior high school students, namely nomophobia, interpersonal conflict, recognition of problems and self-isolation; 3) BK service strategy recommendations include guidance and counseling tailored to the needs. Abstrak: Di tengah pandemi Covid-19, smartphone menjadi piranti utama dalam pembelajaran daring di semua jenjang pendidikan. Hal tersebut berdampak pada intensitas penggunaan smartphone dalam kehidupan sehari-hari. Keadaan tersebut memunculkan perilaku phone snubbing semakin berkembang dan tidak disadari oleh individu. Phone Snubbing sebagai fenomena penggunaan smartphone individu yang berlebihan menunjukan perilaku abai dan tak acuh atas kehadiran orang di sekitar. Perilaku ini ditandai dengan terpaku pada smartphone yang digenggam sehingga dapat menimbulkan dampak positif dan negatif dalam lingkungan sosial, khususnya pada bidang pribadi dan sosial siswa. Penelitian kualitatif deskriptif ini bertujuan untuk menjabarkan informasi tentang latar belakang dan faktor penyebab fenomena perilaku phone snubbing pada siswa serta rekomendasi strategi layanan BK. Analisis data menggunakan model Miles & Huberman. Keabsahan data penelitian dilakukan dengan cara perpanjangan pengamatan, peningkatan ketekunan dan triangulasi sumber. Hasil penelitian menunjukkan 1) Latar belakang perilaku phone snubbing pada siswa SMP menyatakan bahwa penggunaan smartphone dengan kategori tinggi yaitu rata-rata 6-10 jam perhari hingga menyebabkan ketergantungan smartphone yang juga tinggi. Situasi penggunaan smartphone saat interaksi pada siswa SMP sangat beragam, meliputi bentuk penghindaran, untuk mengusir rasa bosan, adanya kepentingan yang terdapat dalam aktivitas dengan smartphone, dan keperluan yang lainnya yang membutuhkan fast response. Alasan penggunaan smartphone untuk memenuhi alih-alih kepentingan belajar juga untuk mencari hiburan, menjaga komunikasi dengan teman jarak jauh. 2) Empat faktor yang mengindikasikan perilaku phone snubbing siswa SMP yaitu nomophobia, konflik interpersonal, pengakuan masalah dan isolasi diri; 3) Rekomendasi strategi layanan BK meliputi bimbingan dan konseling yang disesuaikan dengan kebutuhan.